A drug utilization study of antidepressant drugs in a tertiary care hospital - Yerkade, Vasundhara; Siddiqui, Riyaz Ahmed (International Journal of Basic & Clinical Pharmacology, 2017)
Background: In psychiatric practice, antidepressant drugs are widely used group of drugs. Number of drugs are available in this group with diverse type of mechanisms and efficacy/safety profile. The objective for the study was to identify the prescribing pattern of antidepressant drugs in psychiatric patients at a tertiary care hospital and to see the distribution of antidepressant drugs in the sociodemographic group. Methods: It was a record based descriptive study which was carried out at NKP Salve Institute of Medical Sciences and Research Centre, Nagpur. Case record files of all the patients suffering from depression and other psychiatric disorders and treated with antidepressant drugs during the period of from 1st January 2015 to 31st December 2015 by institutional psychiatrists were analyzed for prescription pattern of antidepressant drugs and their age and sex wise distribution. Results: A total no. of 300 patients received antidepressant drugs. The most commonly prescribed drug was escitalopram in 121 (40.3%) patients followed by fluoxetine in 61 (20.3%) and clomipramine in 30 (10%) patients. Other drugs that were prescribed were mirtazapine in 24 (8%), nortryptiline in 21 (7%), venlafaxine in 13 (4.3%), fluvoxamine in 12 (4%), amitryptiline in 9 (3%), dothiepin in 5 (1.6%) and duloxetine in 4 (1.3%) patients. Also patients in the age group of 31-40 yrs and 21-30 yrs received most number of antidepressants i.e. 129 (40.3%) and 83 (27.6%) patients respectively. Females have received more antidepressant drugs as compared to males. Conclusions: Selective Serotonin Reuptake Inhibitors (SSRIs) are the most commonly prescribed group of antidepressant drugs. Escitalopram followed by Fluoxetine were the most commonly prescribed drugs for the management of depression and other psychiatric disorders because of their better efficacy, safety, tolerability and less side effects as compared to TCAs. Females suffer more from depression and other psychiatric disorders as compared to males and the most vulnerable is 21 to 40 yrs of age.